CHANGES IN FEW PISCINE ENZYMES DUE TO ENDRIN AND SEVIN TOXICOSIS - Thomas, P C; Murthy, T L (Indian Journal of Fisheries, 2011)
The invivo effect of endrin treatment at a dose of 2-3 micrograms per-Kgbody weight, 30 times within a period of 51 days and sevin treatment, 7-8 mg/Kg body weight, 13 times within a period of 21 days on the haemoglobin content,carbonic anyhydrase, catalase and alkaline phosphatase activities in Heteropneiistsfoxsilis is investigated and reported. Hepatic canbonic anhydrase in both endrintreated (gr. 1) and sevin treated (gr. 11) fishes do not show significant alterationsdue to drug treatment. But renal carbonic anhydrase is elevated in both groups.Endrin enhances the hepatic alkaline phosphatase by 29% while renal and intestinalphosphatases are unaffected, Sevin does not alter the liver alkaline phosphatasebut renal enzyme is reduced by 16% while intestinal enzyme is accelerated by33%. Endrin administration enhances the hepatic catalase but reduces the renalenzyme content. Sevin decreases the hepatic catalase content but renal enzyme isaccelerated. The Significance of enzyme enhancement and decreases are discussed.